Progresses in the study of polysaccharide from medicinal plants of the Asclepiadaceae family - He Xiao; Ziqing Zeng; Wenjie Jiang (Pharmaceutical Science Advances)
Medicinal plants from the Asclepiadaceae family, such as Luo Mo (Metaplexis japonica Makino), Xu Changqing (Cynanchum paniculatum), and Bai Wei (Cynanchum atratum Bge.), have long been staples in Traditional Chinese Medicine (TCM) due to their wide range of pharmacological activities (Su et al., 2021) [1]. These beneficial properties are largely attributed to compounds like saponins, alkaloids, and polysaccharides. Polysaccharides, in particular, are vital components in TCM and have garnered increasing attention for their diverse therapeutic effects. Polysaccharides from Asclepiadaceae plants are reported to exhibit a variety of pharmacological activities, including anti-radiation, anti-tumor, anti-fatigue, antioxidant, anti-hyperlipidemic, immune-boosting, and liver-protective effects. These polysaccharides have complex structures made up of different monosaccharides, contributing to their wide range of activities. In this review, we provide a comprehensive summary of the isolation, purification, structural characterization, and pharmacological activities of polysaccharides from medicinal plants in the Asclepiadaceae family. We begin by outlining the methods used for the extraction, isolation, and purification of these polysaccharides. Next, we delve into the pharmacological activities of the isolated polysaccharides. Finally, we discuss the potential clinical applications of these polysaccharides in treating various diseases and highlight areas that require further investigation.